Importance of non-intrinsic platinum dissolution in Pt/C composite fuel cell catalysts. Issue 32 (31st July 2017) - Jovanovič, Primož; Petek, Urša; Hodnik, Nejc; Ruiz-Zepeda, Francisco; Gatalo, Matija; Šala, Martin; Šelih, Vid Simon; Fellinger, Tim Patrick; Gaberšček, Miran
Abstract : On-line analytics provide new insights into the complex interplay of various mechanisms occurring during dissolution of Pt catalyst layers. Abstract : The dissolution of different platinum-based nanoparticles deposited on a commercial high-surface area carbon (HSAC) support in thin catalyst films is investigated using a highly sensitive electrochemical flow cell (EFC) coupled to an inductively coupled plasma mass spectrometer (ICP-MS). The previously reported particle-size-dependent dissolution of Pt is confirmed on selected industrial samples with a mean Pt particle size ranging from 1 to 4.8 nm. This trend is significantly altered when a catalyst is diluted by the addition of HSAC. This indicates that the intrinsic dissolution properties are masked by local oversaturation phenomena, the so-called confinement effect. Furthermore, by replacing the standard HSAC support with a support having an order of magnitude higher specific surface area (a micro- and mesoporous nitrogen-doped high surface area carbon, HSANDC), Pt dissolution is reduced even further. This is due to the so-called non-intrinsic confinement and entrapment effects of the (large amount of) micropores and small mesopores doped with N atoms. The observed more effective Pt re-deposition is presumably induced by local Pt oversaturation and the presence of nitrogen nucleation sites. Overall, our study demonstrates the high importance and beneficial effects of porosity, loading and N doping of the carbon support on the Pt stability in the catalyst layer.